Institutional and actor-oriented factors constraining expert-based forest information exchange in Europe: a policy analysis from an actor-centred institutionalist approach - Baycheva-Merger, Tanya; Sotirov, Metodi Georgiev; Holmgren, Sara; Selter, Andy (2018)
Abstract: Adequate and accessible expert-based forest information has become increasingly in demand for effective decisions and informed policies in the forest and forest-related sectors in Europe. Such accessibility requires a collaborative environment and constant information exchange between various actors at different levels and across sectors. However, information exchange in complex policy environments is challenging, and is often constrained by various institutional, actor-oriented, and technical factors. In forest policy research, no study has yet attempted to simultaneously account for these multiple factors influencing expert-based forest information exchange. By employing a policy analysis from an actor-centred institutionalist perspective, this paper aims to provide an overview of the most salient institutional and actor-oriented factors that are perceived as constraining forest information exchange at the national level across European countries. We employ an exploratory research approach, and utilise both qualitative and quantitative methods to analyse our data. The data was collected through a semi-structured survey targeted at forest and forest-related composite actors in 21 European countries. The results revealed that expert-based forest information exchange is constrained by a number of compound and closely interlinked institutional and actor-oriented factors, reflecting the complex interplay of institutions and actors at the national level. The most salient institutional factors that stand out include restrictive or ambiguous data protection policies, inter-organisational information arrangements, different organisational cultures, and a lack of incentives. Forest information exchange becomes even more complex when actors are confronted with actor-oriented factors such as issues of distrust, diverging preferences and perceptions, intellectual property rights, and technical capabilities. We conclude that expert-based forest information exchange is a complex and challenging task. It is driven by actors’ preferences/interests, perceptions, and capabilities, and is shaped by formal rules and social norms